COMPARATIVE ANALYSIS AND EVALUATION OF THE EFFECTIVENESS OF METHOTREXATE AND LEFLUNOMIDE IN PATIENTS WITH ACTIVE RHEUMATOID ARTHRITIS IN THE CONDITIONS OF CAREFUL CONTROL BASED ON PRINCIPLES OF «TREAT TO TARGET» STRATEGY - S.B. BEKMURODZODA; K.O. SHARIFOV; M.M. MADZHONOVA; YO.U. SAIDOV; KH.R. MAKHMUDOV (Avicenna Tajik State Medical University, 2019)
Objective: To study and evaluate in a comparative aspect the effectiveness of methotrexate (MT) and leflunomide (LEF) in patients with active rheumatoid arthritis (RA) who have indicators of adverse «Treat to target - T2T» strategy. Methods: Monitoring and comparative evaluation of the effectiveness of therapy of modern basic anti-inflammatory drugs in 104 patients with active RA, which, depending on the character of the therapy was randomized and divided into three groups: I (n=34) - Metoject group (MTJ), II (n=36) - MT group and III (n=34) - LEF group. Results: Against the background of the therapy of MTJ, MT and LEF, the patients surveyed showed a statistically significant decrease in both clinicallaboratory activity indicators of RA and the level of pro-inflammatory cytokines (tumor necrosis factor alpha - TNFα, interleukin-6 - IL-6), the positive results of which were most vividly represented in patients of the MTJ group. By the time the study is completed (after 12 months), most patients have achieved the ultimate goal of therapy - a state of low disease activity/remission - and this figure, for I, II and III groups consisted of 78.2%, 73.1% and 44% respectively. Conclusion: The results of the study show a satisfactory performance/tolerability profile of MTJ, MT and LEF in an intensive mode in conditions of close scrutiny based on T2T strategy.